Religious Identity Negotiation in The Translation of Bidāyatul-Hidāyah Book into English - Mukminin, Muhamad Saiful; Irianti, Waviq Alfiana; Layliyah, Imama Nur; Sajarwa, Sajarwa (Universitas Ahmad Dahlan, 2025)
Translating religious text involves negotiating religious identity to convey meaning across different languages and cultures while preserving spiritual values. Despite growing interest in translation studies, limited attention has been given to how this identity negotiation operates in classical Islamic texts. This study examines the negotiation of religious identity in the English translation of Bidayatul-Hidayah by Al-Ghazali and explores the cultural and theological factors that influence this process. Using a quality descriptive method with comparative and interpretative approaches, the study collects data through close reading, identification of religiously nuanced linguistic units, and organisation in a comparison table. The analysis includes the classification of religious identity markers, comparison between the source and target text, and interpretation based on social-cultural and theological context. The findings reveal seven patterns of religious identity negotiations: in religious practice, eschatological terms, moral concepts, religious groups, sacred artefacts, enlightenment terms, and religious figures. These negotiations reflect the cultural, theological, and value-systems differences between Arabic and English. The Study concludes that translating religious text requires a strategic negotiation of meaning to preserve spiritual integrity while ensuring contextual relevance tor the target audience.